(untitled) (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Maruzy A, Susandarini R. 2024. Short Communication: Analysis of simple sequence repeats variations for the assessment of genotypic diversity in Centella asiatica (L.) Urb. Biodiversitas 25: 734-740. Centella asiatica (L.) Urb. is a perennial plant widely known as herbal ingredient in traditional and modern medicine, as well as in the cosmetics industry. This herbaceous species grows in various types of habitat, and is known for its morphological variations among populations, indicating the existence of genotypic variation. In this study, the assessment of genotypic diversity using simple sequence repeats (SSR) was carried out on C. asiatica accessions from 32 populations collected from eight mountains in Central Java. Representative individuals from four populations grow at different altitudes were sampled in each mountain. Amplification of genomic DNA using the SSR primer mCaCIR002 produced a single amplicon of 180 bp. The results of SSR analysis showed that there is high genotypic diversity in C. asiatica which is characterized by variations in the number of microsatellite repeats of (CT)10 to (CT)19. Variations in the number of repeats are mainly caused by insertions and deletions in DNA sequences at the positions 102-145. Haplotype analysis also showed high genetic diversity within and between populations of C. asiatica, indicated by the haplotype diversity of 1.00 in all populations. The haplotype network analysis indicated that there was no gene flow between the four populations at each mountain where C. asiatica populations grow. The results of this study provide evidence for the role of SSR as a suitable molecular marker for studying genotypic diversity at the intraspecific level, and confirming the morphological variability in this species.